The effect of red clover vaginal cream on sexual function in postmenopausal women: A randomized, controlled clinical trial - Jamileh Khayatan; Mina Iravani; Eskandar Moghimipour; Mohammad Hosein Haghighizadeh; Parivash Jelodarian (Mashhad University of Medical Sciences, 2019)
Introduction: Sexual dysfunction in postmenopausal women may decrease their quality of life during this period. Therefore, regarding to the effect of phytoestrogens on the improvement of menopausal symptoms, this study was performed with aim to investigate the effect of red clover vaginal cream on sexual function in postmenopausal women. Methods: This triple-blind clinical trial was conducted in 2018 on 76 postmenopausal women in Ahvaz. Women were randomly divided into two groups: receiving red clover vaginal cream (n=38) and placebo (n=38); they received one applicator of 5 gr vaginal cream every day for 8 weeks. Sexual function was assessed using female sexual function index (FSFI). Data were analyzed by SPSS software (version 22) and using independent t-test, Chi-square, Mann-Whitney, and Wilcoxon tests. PResults: The mean score of all areas of sexual function including: desire, arousal, vaginal moisture, orgasm, sexual satisfaction and pain during intercourse significantly increased after 8 weeks of intervention in both groups that changes were significantly greater in the red clover group (P<0.001). Before the intervention, the mean score of sexual function questionnaire was 9.91± 0.41in the red clover group and 9.77±0.28 in the placebo group; after 8 weeks of intervention, it reached to 28.98±1.72 in the red clover group and 17.59±0.51 in the placebo group. The difference was significantly higher in the red clover group than placebo group (p<0.001). Conclusion: The red clover has beneficial effects on sexual function in postmenopausal women. Therefore, it is recommended as an alternative treatment.